Concordance between Stages of Behavior Change Questionnaire and IPAQ - Nakamura, Priscila Missaki [UNESP]; Papini, Camila Bosquiero [UNESP]; Teixeira, Inaian Pignatti [UNESP]; Sebastiao, Emerson; Gobbi, Sebastiao [UNESP]; Cordeira, Kelly Lynn; Kokubun, Eduardo [UNESP] (Universidade Estadual Paulista (Unesp), Instituto de Biociências, 2013)
A low rate of physical activity (PA) participation is observed worldwide. The identification of feasible and reliable instruments able to accurately measuring PA and help in the development of interventions to promote PA are necessary. This study aimed to analyze the concordance between the Stages of Behavior Change Questionnaire (SBCQ) and the International Physical Activity Questionnaire (IPAQ long-version) in assessing adult leisure-time physical activity (LTPA). A total of 1.588 adults completed the IPAQ to assess LTPA and the participants who performed more than 10 min/week were classified in active individuals. Using the SBCQ, active individuals were those classified in the action or maintenance stage and inactive individuals were those classified in the precontemplation, contemplation or preparation stage. The concordance between SBCQ and IPAQ was found to be 0.80. Separated by gender, it was observed a concordance between the two instruments of 0.82 for women, and 0.77 for men. Regarding age group, it was found to be 0.81 for young and middle-aged adults, and 0.77 for older people. The SBCQ presented a very good concordance with IPAQ to assess LTPA.

Devido à baixa prática de atividade física no mundo, identificar instrumentos que possam avaliar o nível de (AF), além de necessário, podem ajudar no desenvolvimento de intervenções para promoção da AF. Objetivo deste estudo foi analisar a concordância entre o Questionário de Estágio de Mudança de Comportamento (QEMC) e o Questionário Internacional de Atividade Física (IPAQ-versão longa) em avaliar o tempo de atividade física no lazer (AFL). Para avaliar o nível de AFL, 1.588 adultos responderam IPAQ e participantes que realizaram mais de 10 min/ sem foram classificados como ativos. Através do QEM os indivíduos foram classificados no estágio de ação ou manutenção e os inativos classificados no precontemplação, contemplação ou preparação. Concordância entre QEMC e o IPAQ foi 0,80, para as mulheres de 0,82, homens 0,77, adultos e adultos meia idade 0,81 e idosos 0,77. QEMC apresentou boa concordância com IPAQ para avaliar a AFL.
Concordância entre o Questionário de Estágio de Mudança de Comportamento e IPAQ
Concordancia entre el Internado Cuestionario cambio de comportamiento y IPAQ
Keywords: assessment of physical activity; elderly; adults; behavior toward physical activity